2007
DOI: 10.1007/s00213-007-0875-z
|View full text |Cite
|
Sign up to set email alerts
|

AMPA receptor antagonists reverse effects of extended habit training on signaled food approach responding in rats

Abstract: These results indicate that AMPA receptor blockade restores sensitivity to appetitive behavior-disrupting effects of SCH-23390 in subjects exposed to extended training protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Following similar suggestions in the literature (Ashby, Alfonso-Reese, Turken, & Waldron, 1998;Miller, 1981Miller, , 1988, Ashby et al (2007) proposed a model in which the development of automaticity is mediated by a transfer of control from the cortical-striatal pathways emphasized here to cortical-cortical pathways from the relevant areas of sensory cortex to the areas of premotor and motor cortices that mediate the selection and execution of the appropriate motor program. For example, several studies have reported evidence that with overtraining, skills of the type modeled here become independent of both dopamine and the striatum (e.g., Bespalov, Harich, Jongen-Rêlo, van Gaalen, & Gross, 2007;Choi, Balsam, & Horvitz, 2005;Turner, McCairn, Simmons, & Bar-Gad, 2005;Carelli et al, 1997). It would be straightforward to augment the present model with the cortical-cortical pathways proposed by Ashby et al (with cortical-cortical plasticity mediated by Hebbian learning).…”
Section: Limitationsmentioning
confidence: 72%
“…Following similar suggestions in the literature (Ashby, Alfonso-Reese, Turken, & Waldron, 1998;Miller, 1981Miller, , 1988, Ashby et al (2007) proposed a model in which the development of automaticity is mediated by a transfer of control from the cortical-striatal pathways emphasized here to cortical-cortical pathways from the relevant areas of sensory cortex to the areas of premotor and motor cortices that mediate the selection and execution of the appropriate motor program. For example, several studies have reported evidence that with overtraining, skills of the type modeled here become independent of both dopamine and the striatum (e.g., Bespalov, Harich, Jongen-Rêlo, van Gaalen, & Gross, 2007;Choi, Balsam, & Horvitz, 2005;Turner, McCairn, Simmons, & Bar-Gad, 2005;Carelli et al, 1997). It would be straightforward to augment the present model with the cortical-cortical pathways proposed by Ashby et al (with cortical-cortical plasticity mediated by Hebbian learning).…”
Section: Limitationsmentioning
confidence: 72%
“…The goal-directed and habit systems are conceived of as competitors for the control of behavior – the system that is least uncertain about the appropriate behavior given the context may win that competition (Daw et al , 2005). Competition between them can be biased towards the habit system by extended behavioral training (Adams, 1981); boosting synaptic dopamine levels in the striatum (Nelson and Killcross, 2006), or modulating AMPA receptor function (Bespalov et al , 2007). Goal directedness can be rescued by restoring dopamine induced plasticity in the prefrontal cortex (Hitchcott et al , 2007).…”
Section: Explaining Delusion Contentmentioning
confidence: 99%
“…If delusions are learned habits, then pharmacological interventions that restore goal directedness should be effective therapeutically; for example, antagonizing AMPA receptors (Bespalov et al , 2007), boosting PFC dopamine levels (Hitchcott et al , 2007) and attenuating striatal dopamine (Nelson and Killcross, 2006) should favor plasticity and goal directedness. The dopamine partial agonist Aripiprazole combines both antagonism of elevated striatal dopamine and an elevation of attenuated prefrontal dopamine and may specifically target aberrant prediction error signaling in midbrain dopamine neurons (Hamamura and Harada, 2007).…”
Section: Testing the Hypothesismentioning
confidence: 99%
“…For example, some Parkinson's patients are able to emit an automatic motor response when presented with a familiar visual cue (e.g., kicking a ball), despite difficulties in initiating novel voluntary movements [45]. As another example, blockade of D1 receptors strongly disrupts rats' performance of a simple Pavlovian approach response to a sensory cue during early stages of training, but has little or no disruptive effect in rats that receive extended training prior to dopamine antagonist challenge [4647]. …”
Section: Dopamine and Habit Expressionmentioning
confidence: 99%